A label-free impedimetric immunosensor for direct determination of the textile dye Disperse Orange 1 - Yang, Jing; Rocha, Carolina Gomes da [UNESP]; Wang, Shengfu; Ferreira, Antonio Aparecido Pupim [UNESP]; Yamanaka, Hideko [UNESP] (Elsevier B. V., 2015)
A strategy for a label-free impedimetric immunosensor is described for detection of the textile dye Disperse Orange 1 (DO1). The compounds 1,12-diaminododecane (DADD) and then 1,7-diaminoheptane (DAH) were firstly successively grafted onto a glassy carbon electrode (GCE) surface by electro-oxidation of one amino group, while the other terminal amino group was modified with the antibody anti-DO1. The construction process of the immunosensor was characterized by cyclic voltammetry, electrochemical impedance spectroscopy and capacitance measurements. The electron transfer resistance (Rct) exhibited an effective response to the affinity between the immobilized antibody and the antigen in solution. The linear range for the target compound was from 5.0 nmol L(-1) to 0.5 μmol L(-1) (R=0.9980), and the limit of detection (LOD) was 7.56 nmol L(-1). The proposed impedimetric immunosensor has the advantages of simplicity, cost-effectiveness, and sensitivity.
Keywords: Antibody immobilization; Disperse orange 1; Impedimetric immunosensor; Textile dye